“The Friend Zone”- friendship moderates the impact of a web-based group dynamics application on group cohesion: a randomized trial - Thompson, Nicholas Scott (Kansas State University, 2016)
Purpose: Face-to-face group dynamics-based (GDB) programs have been shown to be effective in promoting group cohesion and physical activity (PA). Recent evidence suggests that GDB principles can be successfully translated to web-based applications to impact group cohesion. The social nature of such applications allows for interactions to occur between friends and strangers alike, potentially moderating the effects of such GDB applications. Optimal group composition within GDB web applications has yet to be determined. The present study examines the moderating effects of group composition in a GDB application on group cohesion and PA. Methods: Participants (n = 166) were randomized into same-sex pairs and then randomly assigned to an experimental condition: stranger (no app), stranger (using app), friend (using app) or individual control. Participants in all conditions performed two sets of planking exercises. In between sets, those in partnered conditions interacted with their partner using a GDB social media app, where they participated in a series of team-building activities. The main dependent variables were group cohesion and physical activity, calculated as the total persistence during Block 2, controlling for Block 1 persistence. Results: Results indicate that the group integration dimensions of cohesion were higher in groups that used the application than those that did not (GI-T: p= .001; GI-S: p= .004). Friends that used the app reported greater cohesion across all dimensions than strangers that did the same (ATG-T: p= .006; ATG-S: p= .003; GI-T: p= .001; GI-S: p< .001). There was also a significant difference in PA (p=.004) between the two app-using conditions. However, there was no significant difference in PA between app using conditions and strangers that did not use the app (p= .495). Conclusions: Group cohesion can be enhanced through the use of an online GDB application. Using an online GDB application with a friend is associated with higher levels of cohesion. Further research is necessary to identify effective online GDB applications for impacting physical activity and cohesion in field settings.
Keywords: Cohesion; Physical Activity; Group Dynamics